Criminal Justice System Toward Children With Legal Conflict Seen In Justice Restorative Presfective - Brian Septiadi daud; Irma Cahyaningtyas (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2020)
The criminal justice system of children is very important in the effort to settle cases. Children are gifts of God that are entrusted to be cared for, guarded, and guided for a good future. In article 1 number 1 of Law no. 11 of 2012 states that what is meant by the juvenile justice system is the whole process of resolving cases of children dealing with the law from the investigation stage to the guidance stage after undergoing the crime. The aims of the study were to find out and analyze the juvenile justice system (SPPA) in conflict with the law and to examine the implementation of legal protection against children in conflict with the law based on Law Number 11 of 2012. The research method used to see the arrangement of this arrangement is juridical-normative legal research, this research is research that is attempted with the system reviewing applicable laws and regulations or applied to a particular legal case and concept. The method of collecting legal material with the document method is to collect library research contained in secondary legal materials, then analyzed deductively. The results of this study are to look at the process of the juvenile justice system based on subsystems, components, the process of achieving justice for restorative justice and the process of implementing child protection based on the applicable laws and regulations.